2007
DOI: 10.1103/physrevlett.99.228103
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic Interaction between Two Swimmers at Low Reynolds Number

Abstract: We investigate the hydrodynamic interactions between micro-organisms swimming at low Reynolds number. By considering simple model swimmers, and combining analytic and numerical approaches, we investigate the time-averaged flow field around a swimmer. At short distances the swimmer behaves like a pump. At large distances the velocity field depends on whether the swimming stroke is invariant under a combined time-reversal and parity transformation. We then consider two swimmers and find that the interaction betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
219
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(228 citation statements)
references
References 23 publications
7
219
2
Order By: Relevance
“…For a collection of free swimmers, such as microorganisms [8], hydrodynamic interactions have been shown to lead to instabilities [9,10] that can result in complex dynamical behaviors [10,11]. In the context of simple microswimmer models where hydrodynamic interactions coupled to internal degrees of freedom can be studied with minimal complexity, it has been shown that the coupling could result in complex dynamical behaviors such as oscillatory bound states between two swimmers [12], and collective many-body swimming phases [13,14].A particularly interesting aspect of such hydrodynamic coupling is the possibility of synchronization between different objects with cyclic motions [4,5,[15][16][17][18][19][20][21]. This effect has mostly been studied in simple systems such as two interacting objects or linear arrays and very little is known about possible many-body emergent behaviors of a large number of active objects with hydrodynamic coupling.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For a collection of free swimmers, such as microorganisms [8], hydrodynamic interactions have been shown to lead to instabilities [9,10] that can result in complex dynamical behaviors [10,11]. In the context of simple microswimmer models where hydrodynamic interactions coupled to internal degrees of freedom can be studied with minimal complexity, it has been shown that the coupling could result in complex dynamical behaviors such as oscillatory bound states between two swimmers [12], and collective many-body swimming phases [13,14].A particularly interesting aspect of such hydrodynamic coupling is the possibility of synchronization between different objects with cyclic motions [4,5,[15][16][17][18][19][20][21]. This effect has mostly been studied in simple systems such as two interacting objects or linear arrays and very little is known about possible many-body emergent behaviors of a large number of active objects with hydrodynamic coupling.…”
mentioning
confidence: 99%
“…For a collection of free swimmers, such as microorganisms [8], hydrodynamic interactions have been shown to lead to instabilities [9,10] that can result in complex dynamical behaviors [10,11]. In the context of simple microswimmer models where hydrodynamic interactions coupled to internal degrees of freedom can be studied with minimal complexity, it has been shown that the coupling could result in complex dynamical behaviors such as oscillatory bound states between two swimmers [12], and collective many-body swimming phases [13,14].…”
mentioning
confidence: 99%
“…(1) describes hydrodynamic coupling under the period-averaged flow assumption. However, the phase difference of the microscopic strokes between two swimmers has been shown to actively affect the interaction in unexpected ways, leading to attraction, repulsion, or oscillations [91]. How these subtle swimmer-induced pairwise interactions [77,91] influence the collective behavior of swarms remains to be investigated.…”
Section: -7mentioning
confidence: 99%
“…Furthermore, the collective behavior of many such interacting particles has been explored [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. Collections of self-propelled particles in liquid environment exhibit fascinating and complex nonequilibrium phenomena emerging from self-organization, where hydrodynamic interactions can play a significant role [11,[36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52].…”
Section: Introductionmentioning
confidence: 99%
“…form-stable) artificial microswimmers, several examples of microswimmers were identified that actively deform to achieve self-propulsion. Many biological microorganisms fall into this category [64][65][66], as well as several instances of proposed theoretical model microswimmers [40,[67][68][69][70][71]. Apart from that, microswimmers can be realized in the form of soft particles that are already de- * Electronic address: kuechler@thphy.uni-duesseldorf.de † Electronic address: menzel@thphy.uni-duesseldorf.de formable in their non-propelling passive state.…”
Section: Introductionmentioning
confidence: 99%